2015
DOI: 10.1371/journal.pone.0128800
|View full text |Cite
|
Sign up to set email alerts
|

Religious Involvement and Mental Disorders in Mainland China

Abstract: PurposeThe present study aims to examine the association between religious involvement and mental disorder (anxiety disorder, mood disorder, alcohol use disorder) in a general Chinese population, and explore connections between religious belief and mental disorders in the Hui and Han ethnic groups.MethodData were examined from a representative sample of 2,770 community-dwelling adults in the province of Ningxia located in western China. Self-reported religious attendance and the importance of religious in dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
(44 reference statements)
0
15
0
1
Order By: Relevance
“…Interestingly, this discrepant finding is consistent with data on other published studies on spirituality and mental health in China. Wang et al (2015) observed that importance of religion and religious service attendance in a community population in China directly correlated with incidence of psychopathology, particularly anxiety disorders. In addition, Zhang and colleagues (Zhang and Xu, 2007; Zhang et al, 2011) found that, among Chinese rural women, those who had suicidal intentions and committed suicide were more likely to be religiously affiliated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this discrepant finding is consistent with data on other published studies on spirituality and mental health in China. Wang et al (2015) observed that importance of religion and religious service attendance in a community population in China directly correlated with incidence of psychopathology, particularly anxiety disorders. In addition, Zhang and colleagues (Zhang and Xu, 2007; Zhang et al, 2011) found that, among Chinese rural women, those who had suicidal intentions and committed suicide were more likely to be religiously affiliated.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling process has been described elsewhere [19]. First, 62 primary sampling units (PSUs) were selected from 2,602 primary units (include 2209 villages and 393 neighborhood communities) using a probability proportional to size method.…”
Section: Methodsmentioning
confidence: 99%
“…Often, mixed results have been reported. Some reports focused on the association of religion and mental disorders among some subpopulation groups, such as rural women (Liu and Mencken 2010;Liu 2011;Wei and Liu 2013;Wang et al 2015). More recent studies using nationally representative population samples found a positive relationship between religion and SWB in China (Chen and Williams 2016;He et al 2016;Lu and Zhang 2016).…”
Section: Religion Background In Chinamentioning
confidence: 99%